Research groups' social capital: a clustering approach - Ziherl, Petra (Metodološki zvezki, 2006)
Our purpose in this article is to study the characteristics of a research group's social capital. We proceed from the theoretical distinctions made in the literature on social capital, such as weak against strong ties, structural holes against cohesion and homogeneity against heterogeneity of a group. We assume that research groups differ systematically with respect to the kind of social capital they possess, which has an impact on the scientific performance of the members of these groups. Social capital of research groups is conceptualized in terms of complete networks. We use the data from the Slovenian study of academic research groups conducted in 2003/2004. Research groups include Ph.D. students, their supervisors, and other researchers. They are representative of the Slovenian research groups, which include Ph.D. students under the "junior researchers" program financed by the Slovenian Ministry of Technology and Higher Education. We explore the variation in research groupsć social capital by using a clustering approach. The analysis reveals three types of research group's social capital: weak social capital, strong social capital of a bonding kind, and strong social capital of a bridging type. Research groups with weak social capital are small, and cooperation ties among group members are weak. Bonding social capital is characteristic for small research groups with strong cooperation ties, which are embedded in a dense network structure. Bridging social capitalis found in research groups which consist of a larger number of researchers from different institutions connected with one another with ties of a moderate strength. The network structure in the latter case shows structural holes. In the last part of the paper, we ask whether scientific performance of Ph.D. students varies according to the social capital of their research groups. We found that students who are involved in research groups with bridging social capital show significantly better performance than students who are members of the groups with either bonding or weak social capital. The relationship between the strength of ties and performance seems to be non-linear: it is the moderate strength of social ties and moderate group cohesiveness, which comes along the cooperation across different institutions and disciplines, that is the most beneficial for the performance of Ph.D. students.
Keywords: Raziskovalci; Researchers; Social networks; Družbena omrežja; socialni kapital; družboslovno raziskovanje